Hydrogen Sulfide-Mediated Polyamines and Sugar Changes Are Involved in Hydrogen Sulfide-Induced Drought Tolerance in Spinacia oleracea Seedlings - Chen, Juan; Shang, Yu-Ting; Wang, Wen-Hua; Chen, Xi-Yan; He, En-Ming; Zheng, Hai-Lei; Shangguan, Zhouping (Frontiers in Plant Science, 2016)
Hydrogen sulfide (H2S) is a newly appreciated participant in physiological and biochemical regulation in plants. However, whether H2S is involved in the regulation of plant responses to drought stress remains unclear. Here, the role of H2S in the regulation of drought stress response in Spinacia oleracea seedlings is reported. First, drought stress dramatically decreased the relative water content (RWC) of leaves, photosynthesis, and the efficiency of PSII. Moreover, drought caused the accumulation of ROS and increased the MDA content. However, the application of NaHS counteracted the drought-induced changes in these parameters. Second, NaHS application increased the water and osmotic potential of leaves. Additionally, osmoprotectants such as proline and glycinebetaine (GB) content were altered by NaHS application under drought conditions, suggesting that osmoprotectant contributes to H2S-induced drought resistance. Third, the levels of soluble sugars and polyamines (PAs) were increased differentially by NaHS application in S. oleracea seedlings. Moreover, several genes related to PA and soluble sugar biosynthesis, as well as betaine aldehyde dehydrogenase (SoBADH), choline monooxygenase (SoCMO), and aquaporin (SoPIP1;2), were up-regulated by H2S under drought stress. These results suggest that H2S contributes to drought tolerance in S. oleracea through its effect on the biosynthesis of PAs and soluble sugars. Additionally, GB and trehalose also play key roles in enhancing S. oleracea drought resistance.